Africa's Orphans and Vulnerable Children - Subbarao, K.; Mattimore, A.; Plangemann, K. (2012)
The note is based on the "Social Protection of Africa's Orphans and vulnerable children" study, which looks at HIV/AIDS, and the violent conflicts that are giving rise to a massive generation of orphans in Sub-Saharan Africa. The region currently has about 12 million orphans, most under the age of fifteen. Coping with the risks, and consequences of orphan-hood, poses immense problems: resources are limited, communities are being overwhelmed, and the realization of international development goals is being threatened. Yet, the contours of public action are unclear due to limited knowledge of the problem's magnitude, and a lack of clarity on the effectiveness of interventions. While the impact of the epidemic is felt throughout communities, the focus of the study is limited to the analysis of the implications of the growing numbers of vulnerable children for Africa's future human development. The study pulls together the existing information on orphans, and vulnerable children, traces the sources, and extent of their vulnerability, examines the prevailing community responses, and, argues the case for concerted public actions. It also reviews the ongoing interventions, and delineates some examples of good practices. Hopefully, enhanced policy-making capacities will offer effective social protection to these groups in Sub-Saharan Africa.